Crystal Facet Engineering Induced Active Tin Dioxide Nanocatalysts for Highly Stable Lithium–Sulfur Batteries. Issue 48 (6th November 2021) - Jiang, Bo; Qiu, Yue; Tian, Da; Zhang, Yu; Song, Xueqin; Zhao, Chenghao; Wang, Maoxu; Sun, Xun; Huang, Huihuang; Zhao, Chenyang; Zhou, Hao; Chen, Aosai; et al.
Abstract: Controlling exposed crystal facets through crystal facet engineering is an efficient strategy for enhancing the catalytic activity of nanocrystalline catalysts. Herein, the active tin dioxide nano–octahedra enclosed by 332 crystal facets (SnO2 332) are synthesized on reduced graphene oxide and demonstrate powerful chemisorption and catalytic ability, accelerating the redox kinetics of sulfur species in lithium–sulfur chemistry. Attributed to abundant unsaturated–coordinated Sn sites on 332 crystal planes, SnO2 332 has outstanding adsorption and catalytic properties. The material not only adsorbs and converts polysulfides efficiently, but also prominently lowers the decomposition energy barrier of Li2 S. The batteries with these high active electrocatalysts exhibit excellent cycling stability with a low capacity attenuation of 0.021% every cycle during 2000 cycles at 2 C. Even with a sulfur loading of 8.12 mg cm −2, the batteries can still cycle stably and maintain a prominent areal capacity of 6.93 mAh cm −2 over 100 cycles. This research confirms that crystal facet engineering is a promising strategy to optimize the performance of catalysts, deepens the understanding of surface structure‐oriented electrocatalysis in Li–S chemistry, while aiding the rational design of advanced sulfur electrodes. Abstract : Highly active SnO2 nanocatalysts enclosed by high‐index 332 crystal facets are fabricated via crystal facet engineering to improve the performance of lithium–sulfur batteries. SnO2 (332) crystal facets with abundant unsaturated–coordinated Sn sites not only are highly active for adsorption of lithium polysulfides (LiPSs) but also have robust catalytic activity to expedite transformations of LiPSs and Li2 S decomposition.